A comparison of diversity and catch composition of mini trawl (arad) and lift net (bagan) in Cilincing, Jakarta Bay, Indonesia - TRI DEWI KUSUMANINGRUM PRIBADI; ROZA YUSFIANDAYANI; DOMU SIMBOLON; MERCY PATANDA; RACHMAD CAESARIO; ELNOSAN JEMBAR SAYIDINA; SUSANTI RAHAYU VIOLITA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Pribadi TDK, Yusfiandayani R, Simbolon D, Patanda M, Caesario R, Sayidina EJ, Violita SR. 2024. A comparison of diversity and catch composition of mini trawl (arad) and lift net (bagan) in Cilincing, Jakarta Bay, Indonesia. Biodiversitas 25: 265-277. Arad is a traditional fishing gear that is still popular and widely used in Indonesia, including in Cilincing, the bay in the northern part of Jakarta. Even though the Indonesian government has prohibited this fishing gear, the discarded fishing gear is still utilized by many fishers due to its effective result in getting a large volume of fish caught. A study on the diversity and catch composition of arad (trawl) and bagan (lift net) fishing gear was conducted between January and June 2024 in Cilincing waters to represent active and passive fishing gear. Samples of fish caught from both fishing gears were observed directly, while interviews with the fishers were conducted to get further information on their view. The study showed that in comparison to bagan, arad caught more species, including reef fish. Both fishing gear caught fin-fish and non-finfish (mollusk, crustacean, jellyfish) in different proportions. The data showed that arad caught more species (28) compared to bagan (18). Arad caught mostly demersal fish (57.14%), while bagan mostly caught pelagic fish (53.33%). The value of Total Length (TL) of fish caught by both fishing gears was mostly under the Length of First of Maturity (LM). Referring to the list issued by IUCN, most of the species caught by arad and bagan were in the Least Concern status of conservation, and neither CITES nor the Indonesian Ministry of Environment and Forestry has issued any information regarding the population status.